Case Report: Changes in Regional Cerebral Blood Flow in Chronic Akathisia of a Depressed Patient Before and After Electroconvulsive Therapy Treatment - Suzuki, Akihito; Kobayashi, Ryota; Shirata, Toshinori; Komoriya, Hitomi; Kanoto, Masafumi; Otani, Koichi (Frontiers in Psychiatry, 2021)
Akathisia, which characterized by subjective restlessness and objective hyperactivity, is induced mostly by antipsychotics and antidepressants. Chronic akathisia is defined as persistence of symptoms for more than 3 months. The pathophysiology of chronic akathisia remains unclear. This report describes a depressed patient, a 66-year-old woman with a diagnosis of major depressive disorder, with chronic akathisia. Her regional cerebral blood flow (rCBF) was measured using single photon emission computed tomography (SPECT) before and after the treatment with electroconvulsive therapy (ECT). She had experienced akathisia three times prior because of risperidone, escitalopram, and clomipramine administration. After levomepromazine was added to quetiapine to treat insomnia, she developed akathisia symptoms such as a sense of restlessness and inability to sit in one place for a few minutes. These antipsychotics were withdrawn. Propranolol was administered, leading to no apparent improvement for eight months. After she was diagnosed as having major depressive disorder and chronic akathisia, she received 10 sessions of bilateral ECT. Her depressive symptoms improved greatly. Akathisia disappeared completely after ECT. SPECT revealed that rCBF was decreased in the middle frontal gyrus and parietal lobe, that it was increased in the thalamus, fusiform gyrus, and cerebellum before ECT, and that these abnormalities in rCBF were approaching normal levels after ECT. Findings presented in this report suggest ECT as a beneficial treatment for chronic akathisia. Altered rCBF in the middle frontal gyrus, parietal lobe, thalamus, fusiform gyrus, and cerebellum, and especially decreased rCBF in the parietal lobe, may be related to the pathophysiology of chronic akathisia.